The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ijfoodmicro.2020.108642
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis and Hysterothylacium species in Mediterranean and North-East Atlantic fishes commonly consumed in Spain: Epidemiological, molecular and morphometric discriminant analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The prevalence of Anisakis larvae and infection intensity in wild fish vary according to species, fishing area, season and individual characteristics of the fish 3,23 . As in the vast majority of marine fish, blue whiting tend to accumulate Anisakis larvae in their visceral organs, 23,33 which were the most parasitized part of the fish in this study. However, larval migration to the flesh also constitutes an important source of infection, reflected in the high number of larvae detected in the anterior ventral musculature.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The prevalence of Anisakis larvae and infection intensity in wild fish vary according to species, fishing area, season and individual characteristics of the fish 3,23 . As in the vast majority of marine fish, blue whiting tend to accumulate Anisakis larvae in their visceral organs, 23,33 which were the most parasitized part of the fish in this study. However, larval migration to the flesh also constitutes an important source of infection, reflected in the high number of larvae detected in the anterior ventral musculature.…”
Section: Discussionmentioning
confidence: 67%
“…The parasitic load in the musculature decreases towards the posterior end of the fish, and the anterior dorsal and posterior musculature are considered the safest parts for human consumption because of the absence or low number of larvae detected 34 . Other studies using visual inspection have reported similar Anisakis larval distribution in this host species in specimens from different fishing areas 23,35,36 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this pelagic fish, the genera Anisakis, Contracaecum, Hysterothylacium, and Pseudoterranova have been reported [5,32]. For the genus Anisakis, prevalence oscillates from 65 to 99.5 % for the area north of Spain [25,29,33].…”
Section: Introductionmentioning
confidence: 81%
“…The higher incidence in Spain can be chiefly attributed to the country's culinary traditions, with most infections deriving from the popular consumption of European anchovies (Engraulis encrasicolus) and European pilchard (Sardina pilchardus), marinated in vinegar [2,22]. Other fish which are widely consumed in Spain include blue whiting (Micromesistius poutassou), horse mackerel (Trachurus trachurus), European hake (Merluccius merluccius), and Atlantic bonito (Sarda sarda), and these present high infection rates for ascaridoid larvae [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%